Performance of academic leaders and their role in achieving the requirements of organizational excellence for Palestinian universities from the faculty members' point of view (Palestine Technical College Journal for Research and Studies, 2021)
The study aimed to identify the level of academic leaders and their role in the requirements of organizational distinction for Palestinian universities from the point of view of faculty members, and by using the descriptive approach, and with reference to the previous literature, a questionnaire consisting of (54) items distributed into (5) fields was conducted, namely: (Performance of academic leaders And distinction in service provision, distinction in organizational structure, technological distinction, and technological distinction. The study found that the performance level of academic leaders in Palestinian universities was high, and the degree of availability of organizational excellence requirements in Palestinian universities was high. Also, a positive correlation relationship with statistical significance was found between the performance of academic leaders in Palestinian universities, and the degree of availability of organizational distinction requirements in In light of these results, the study recommended the necessity of holding specialized training courses for academic leaders.
Keywords: Academic Leadership; Organizational distinction; Palestinian Universities